2016
DOI: 10.1016/j.ajog.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Location of childbirth for rural women: implications for maternal levels of care

Abstract: BACKGROUND A recent American College of Obstetricians and Gynecologists and Society for Maternal Fetal Medicine consensus statement on levels of maternity care lays out designations that correspond to specific capacities available in facilities that provide obstetric care. Pregnant women in rural and remote areas receive particular attention in discussions of regionalization and levels of care, owing to the challenges in assuring local access to high-acuity services when necessary. Currently, approximately hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 27 publications
4
54
1
Order By: Relevance
“…This information represents the demographic information for the community surrounding the hospital and provides a proxy for the patients served by the hospital. While many factors influence patients' hospital utilization, studies have shown travel distance is a significant determinant of hospital utilization (Friedman et al, ) and the majority of women deliver at their local hospital (Kozhimannil, Casey, Hung, Prasad, & Moscovice, ). Demographic variables were calculated and expressed as a proportion of the population of interest.…”
Section: Methodsmentioning
confidence: 99%
“…This information represents the demographic information for the community surrounding the hospital and provides a proxy for the patients served by the hospital. While many factors influence patients' hospital utilization, studies have shown travel distance is a significant determinant of hospital utilization (Friedman et al, ) and the majority of women deliver at their local hospital (Kozhimannil, Casey, Hung, Prasad, & Moscovice, ). Demographic variables were calculated and expressed as a proportion of the population of interest.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, access to hospital‐based obstetric care is declining in rural United States counties; currently, fewer than half of rural counties have a hospital that provides obstetric services . And, approximately 1 in 4 pregnant rural residents give birth in nonlocal hospitals, often owing to the clinical necessity of higher‐acuity care, which is frequently not available in rural communities . Clinical recommendations for perinatal regionalization support nonlocal childbirth for rural residents with pregnancy complications and those who require higher‐acuity neonatal care .…”
mentioning
confidence: 99%
“…Approximately one‐fourth of American women reside in rural areas and most of these women must drive at least 1 hour to access health care . Women in rural areas experience poorer health outcomes including higher rates of cerebrovascular disease deaths and cervical cancer …”
mentioning
confidence: 99%
“…Women residing in rural areas are more likely to initiate prenatal care after the first trimester and may have increased pregnancy complications . Pregnancy complications requiring a higher level of care may require rural women to travel long distances . HIV is considered a high‐risk pregnancy condition, but little information is available regarding pregnancy outcomes among women living with HIV in relation to rural residence…”
mentioning
confidence: 99%
See 1 more Smart Citation